A study on the clinical profile of children with snake envenomation in a tertiary referral centre at Dharmapuri, Tamilnadu, India - K. S., Kumaravel; J., Ganesh (International Journal of Research in Medical Sciences, 2017)
Background: Snake envenomation is a well-known cause of morbidity and mortality in rural India. In the year 2009, WHO included snake bite in the list of neglected diseases. Methods: This study was conducted in children admitted with snake bite in Pediatric Intensive Care Unit in the year 2015. Their demographic details, site of bite, arrival time, 20Minutes Whole Blood Cloting Time, Clinical signs and symptoms, complications and outcome were measured. Results: The male: female ratio was 2.57:1. Peak age group affected was 6 to 12 years old children. Lower limbs were commonly bitten. 65% of children arrived in the hospital between 6 and 24 hours after the bite. Pain and swelling at the site of bite were the most common symptom of envenomation. 80% of envenomation was found to be hematotoxic, 11% of envenomation was neurotoxic and 68% of children were successfully treated with 10 vials of ASV. There was only one death during the study period. Conclusion: This study reiterates the need for a more rapid transport and administration of ASV in the transit period. Other important observations in the study are that the number of neurotoxic snake bites is only 9% and the presence of allergic reactions to ASV in 6% of children. The development of monovalent ASV specific to the snake species may be considered, which will be associated with less anaphylaxis and more effective neutralisation of venom.